Clinical and Radiographic Evaluation of Early Loaded Maxillary Anterior Implants: Three-Year Follow-up - KAHRAMANOĞLU, ERKUT; ÖZKAN, YASEMİN; ASLAN, YILMAZ UMUT; ÖZKAN, YAŞAR (QUINTESSENCE PUBLISHING CO INC, 2019)
The aim of this study was to evaluate clinical and radiologic results up to 3 years in patients treated with early loading of anterior implants supporting single-tooth all-ceramic restorations. Twenty-four patients were treated with 29 screw-type implants in the anterior maxilla. The implants were evaluated by clinical and radiographic parameters. Clinical parameters Plaque Index (PI), Sulcus Bleeding Index (BI), peri-implant probing depth (PD), and marginal bone loss (MBL) were recorded. At the recall examinations, all implants were successfully integrated, demonstrating healthy peri-implant soft tissues as documented by standard clinical parameters. No biologic complications were observed. There was no statistically significant increase in MBL between the baseline and recall stages (P >.05). Early loaded maxillary anterior implants supporting single-tooth restorations reveal successful clinical and radiographic outcomes when treatment steps were performed.
Keywords: MARGINAL BONE LEVEL; PARTIALLY EDENTULOUS PATIENTS; SINGLE-TOOTH IMPLANTS; IMMEDIATE; ABUTMENT; REGENERATION; STABILITY; SYSTEMS